The merger of departments across universities: The case of veterinary schools in Japanese national universities. (November 2018) - Yoshinaga, Keiichiro
Highlights: Market need and international standards are changing veterinary education. The existing veterinary schools in Japan cannot cope with the changes. Departmental mergers across universities are the solution. Joint degree programs in veterinary schools enlarged the concept of merger. Abstract: With the rise of neoliberalism, institutional mergers are often discussed and carried out in higher education. Among merger cases, this paper will focus on the departmental mergers across universities that have not been discussed. To discuss departmental mergers, the paper will pick up the case of the merger of departments of veterinary medicine in Japan. It will reveal many issues surrounding departmental mergers and veterinary medicine; universities' control of budgets and personnel, faculty members' academic interest, the switch to practical training because of changing social needs, professional associations' and local communities' influence as stakeholders, the stronger autonomy of the university than the power of the Ministry of Education (after 2001, the MEXT: the Ministry of Education, Culture, Sports, Science, and Technology), and international standards of veterinary medicine. The merger attempts led to joint undergraduate degree programs, in which two departments were combined but each remained in its original university. This partially addressed issues of size and clinical training. It can be called another type of merger. From the perspective of educational development, the case has many implications for the reorganization of the existing departments of veterinary medicine in Asia, most of which are smaller in size than their American counterparts. It is also significant to the departments of other disciplines, that are struggling to improve their standings because of their small size.